Community structures of endoparasitic helminths of Channa punctatus from a fresh water river and a polluted lagoon of Bangladesh (Bangladesh Journal of Zoology, 2012)
Community structures of the parasites of Channa punctatus collected from fresh water Ichamoti river (IR) and a polluted sewerage treatment lagoon (SL) near Dhaka city were determined. Out of the total 104 C. punctatus fish observed, 78.85% were parasitized by at least one species of helminth endoparasites. Twelve metazoan endoparasite (viz. six trematodes, one cestode, three nematodes and two acantho-cephalans) were recorded. Neopecoelina saharanpuriensis, Pallisentis nandai, P. ophiocephali, Ascaridia sp. were common in both sites. Euclinostomum heterostomum, an unidentified digenean, Genarchopsis ozakii, Gangesia bengalensis, Buckleynema channi were recorded from IR and Genarchopsis bangladensis, Phyllodistomum chauhani, Camallanus intestinalus from the SL fishes. Trematode was the most prevalent group and had 63.46% and 53.85% prevalence in IR and SL sample fishes, respectively. Among the parasites of IR sample, only E. heterostomum was accounted as secondary and others fall in the satellite species category; no central species accounted in the sample. In case of SL sample, no parasite species found central, Pallisentis spp. could be considered secondary and others as satellite species. A significant positive correlation was observed between the standard length of the host, and the abundance and prevalence found only for Pallisentis spp. in SL fishes, and between the standard length and the abundance of the Ascaridia sp. in IR fishes. The larger hosts were more infected than the smaller hosts. Parasites of the fish of both sites showed typical over-dispersed distribution pattern in both the sites. No parasite showed random or uniform distribution in both the sample fishes. Parasite species richness index was lower in SL sample. Prevalence and intensity were higher in both sexes in SL sample than those of in IR sample.DOI: http://dx.doi.org/10.3329/bjz.v39i2.10584 Bangladesh J. Zool. 39(2): 173-185, 2011